Dimethyl Sulfoxide Attenuates Radiation-Induced Testicular Injury through Facilitating DNA Double-Strand Break Repair. (20th June 2022) - Huang, Zeze; Peng, Renjun; Yu, Huijie; Chen, Zhongmin; Wang, Sinian; Wang, Zhengming; Dong, Suhe; Li, Wei; Jiang, Qisheng; Li, Fengsheng; Li, Quanmin
Abstract : The testis is susceptible to ionizing radiation, and male infertility and sexual dysfunction are prevalent problems after whole-body or local radiation exposure. Currently, there is no approved agent for the prevention or treatment of radiation-induced testicular injury. Herein, we investigated the radioprotective effect of dimethyl sulfoxide (DMSO), an organosulfur compound that acts as a free radical scavenger, on testicular injury. Treatment of mice with a single dose of DMSO prior to 5 Gy irradiation restored sex hormones and attenuated the reduction in testis weight. Histological analyses revealed that DMSO alleviated the distorted architecture of seminiferous tubules and promoted seminiferous epithelium regeneration following irradiation. Moreover, DMSO provided quantitative and qualitative protection for sperm and preserved spermatogenesis and fertility in male mice. Mechanistically, DMSO treatment enhanced GFR α -1 + spermatogonial stem cell and c-Kit + spermatogonial survival and regeneration after radiation. DMSO also alleviated radiation-induced oxidative stress and suppressed radiation-induced germ cell apoptosis in vivo and in vitro . Additionally, DMSO efficiently reduced DNA damage accumulation and induced the expression of phosph-BRCA1, BRCA1, and RAD51 proteins, indicating that DMSO facilitates DNA damage repair with a bias toward homologous recombination. In summary, our findings demonstrate the radioprotective efficacy of DMSO on the male reproductive system, which warrants further studies for future application in the preservation of male fertility during conventional radiotherapy and nuclear accidents.